Identification of a Triple Drug Combination That Is Synergistically Cytotoxic for Triple-Negative Breast Cancer Cells Using a Novel Combination Discovery Approach. (September 2020) - Ahmad, Syed; He, Qingping; Williams, Kevin P.; Scott, John E.
Triple-negative breast cancer (TNBC) is a very aggressive form of breast cancer with few molecularly targeted therapies. We used a novel unbiased approach to identify higher-order synergistic or enhancer combinations of marketed kinase inhibitor drugs that inhibit cell viability of TNBC cell lines. We mixed all 33 kinase-targeted drugs on the market at the time of this study, which allowed for all possible combinations to exist in the initial mixture. A kinase inhibitor group dropout approach was used to identify active groups and then single active drugs. After only three rounds of deconvolution, we identified five single drugs to test further. After further testing, we focused on one novel subset consisting of three kinase inhibitor drugs: dasatinib, afatinib, and trametinib (DAT) that target src family kinases, HER2/EGFR, and MEK, respectively. The DAT combination potently inhibited the proliferation of three TNBC cell lines and modestly inhibited a fourth. However, it was not significantly more potent or synergistic than other two drug combinations of these drugs. The cytotoxic activities of all possible combinations of these three drugs were also analyzed. Compared with all two-way combinations, the three-way DAT combination generated the most cytotoxicity and the highest synergies for two of the four cell lines tested, with possibly mild synergy in a third cell line. These data indicated that the DAT combination should be evaluated for efficacy in an in vivo model of TNBC and may provide a novel combination of existing drugs for the treatment of a subset of TNBC cases.